Attachment as a factor in generating satisfaction with, and loyalty to, rural tourism destinations - Campón-Cerro,Ana María (2015)
Place attachment has recently become a research topic of interest as a relevant concept in understanding some tourist behaviours. It is a relational concept based on cognitive and emotional connections with destinations, yet it has seldom been studied as a loyalty predictor. The objective of this research is to test the influence that attachment exerts on satisfaction with, and loyalty to, rural tourism destinations, through attachment´s main dimensions: identity and destination dependence. The application of attachment to rural tourism is considered interesting because of the particular relationships that tourists establish with the associated environments. In addition, this field lacks causal studies related to marketing, to better plan, manage and commercialise these destinations and their companies. To test the theoretical model, a sample of data on 464 rural tourists was collected through an on-line survey. An analysis was carried out using a Partial Least Squares (PLS) technique through structural equation modelling. The results reveal that both destination identity and dependence are significant antecedents of overall satisfaction with, and loyalty to, rural tourism destinations, but destination dependence has a greater influence. The model shows a good capability to explain the endogenous constructs of overall satisfaction and loyalty.